2018
DOI: 10.1029/2018wr022768
|View full text |Cite
|
Sign up to set email alerts
|

Fiber‐Optic Sensing for Environmental Applications: Where We Have Come From and What Is Possible

Abstract: The use of fiber‐optic sensors has flourished in many fields over the past 30 years. One particular branch of fiber‐optic sensing, distributed temperature sensing, has become a well‐explored and widely‐accepted tool for a diverse range of environmental applications over the past decade. Peer‐reviewed work on fiber‐optic distributed temperature sensing advanced significantly, moving from innovations in instrumentation, deployment techniques, calibration, and analysis methods to applications. However, exciting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…This study suggested that distributed strain sensing, as an emerging application of fiber optic sensing (Shanafield et al, 2018), has the potential to provide not only geomechanical information, which gives critical constraints in geomechanical risk assessments of subsurface fluid injection and extraction operations (Burghardt, 2018) and landslides (Kogure & Okuda, 2018), but also unique insights into the hydromechanical link between fluid flow and rock deformation. The information derived from such monitoring may 10.1029/2019WR024795…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that distributed strain sensing, as an emerging application of fiber optic sensing (Shanafield et al, 2018), has the potential to provide not only geomechanical information, which gives critical constraints in geomechanical risk assessments of subsurface fluid injection and extraction operations (Burghardt, 2018) and landslides (Kogure & Okuda, 2018), but also unique insights into the hydromechanical link between fluid flow and rock deformation. The information derived from such monitoring may 10.1029/2019WR024795…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in airborne and fiber optic (FO) techniques have enabled distributed temperature sensing (DTS). In the case of FO‐based DTS, for example, temperature changes can be recorded continuously in space and in time (Shanafield et al, ; Vogt et al, ). Temperature measured with airborne hyperspectral and near‐infrared cameras, on the other hand, allows for the generation of detailed maps of surface temperature, albeit at lower temporal resolution than with FO‐DTS (Cardenas et al, ).…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
“…Over the last decade, the ability of this tool in hydrology has been widely demonstrated [3], especially for soil moisture determination [4,5], surface waters monitoring [6,7], hydrogeological applications [8], and at the groundwater-surface water interface [9][10][11]. In a commentary, Shanafield et al highlighted the increase of environmental application of DTS and identified around 500 peer-reviewed articles published in hydrologic applications in seven years [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DTS instrument manufacturers define the specifications of each DTS device, including the minimum sampling interval and the spatial resolution. For Raman spectra DTS, the highest performing devices can provide a 0.125 m sampling interval with a 0.29 m spatial resolution, whereas some devices provide a 2 m sampling interval with a 4 m spatial resolution [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation